Pengaruh Kosentrasi Pure Kundur (Benincasa hispida) dan Agar-Agar Terhadap Mutu Kimia dan Organoleptik Panna Cotta Vegan - Kosasih, Michael Fidellouis; Hartati, Fadjar Kurnia; Rahmiati, Retnani (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to develop a vegan panna cotta using winter melon (Benincasa hispida), non-dairy cream, soy milk, and agar-agar, focusing on improving nutritional value and organoleptic acceptability. A Completely Randomized Design (CRD) with a single factor and four treatments was employed: P1 (40 g winter melon puree, 2 g agar-agar), P2 (40 g winter melon puree, 3 g agar-agar), P3 (60 g winter melon puree, 2 g agar-agar), and P4 (60 g winter melon puree, 3 g agar-agar). The analyses included vitamin C content, crude fiber, fat content, and organoleptic evaluations of taste and texture. The results revealed that: (1) P3 showed the best performance, with the highest vitamin C and crude fiber content and the best organoleptic scores for taste and texture; (2) Effectiveness tests also ranked P3 as the most optimal formulation with the highest total effectiveness score (0.9478); (3) P4 excelled in vitamin C and crude fiber content but scored lower in organoleptic properties compared to P3; (4) P1 and P2 demonstrated less optimal performance across various parameters. Thus, the P3 formulation (60 g winter melon puree and 2 g agar-agar) is recommended as the best formulation for producing high-quality vegan panna cotta in terms of nutritional value and organoleptic acceptability. This product has the potential to become a healthy, eco-friendly dessert innovation with high nutritional value, catering to the needs of modern consumers.